Activation of PAR4 Upregulates p16 through Inhibition of DNMT1 and HDAC2 Expression via MAPK Signals in Esophageal Squamous Cell Carcinoma Cells - Ming Wang; Shuhong An; Diyi Wang; Haizhen Ji; Xingjing Guo; Zhaojin Wang (Journal of Immunology Research)
A previous study showed that a downexpression of protease-activated receptor 4 (PAR4) is associated with the development of esophageal squamous cell carcinoma (ESCC). In this study, we explored the relationship between PAR4 activation and the expression of p16, and elucidated the underlying mechanisms in PAR4 inducing the tumor suppressor role in ESCC. ESCC cell lines (EC109 and TE-1) were treated with PAR4-activating peptide (PAR4-AP). Immunohistochemistry for DNA methyltransferase 1 (DNMT1) and histone deacetylase 2 (HDAC2) was performed in 26 cases of ESCC tissues. We found that DNMT1 and HDAC2 immunoreactivities in ESCC were significantly higher than those in adjacent noncancerous tissues. PAR4 activation could suppress DNMT1 and HDAC2, as well as increase p16 expressions, whereas silencing PAR4 dramatically increased HDAC2 and DNMT1, as well as reduced p16 expressions. Importantly, the chromatin immunoprecipitation-PCR (ChIP-PCR) data indicated that treatment of ESCC cells with PAR4-AP remarkably suppressed DNMT1 and HDAC2 enrichments on the p16 promoter. Furthermore, we demonstrated that activation of PAR4 resulted in an increase of p38/ERK phosphorylation and activators for p38/ERK enhanced the effect of PAR4 activation on HDAC2, DNMT1, and p16 expressions, whereas p38/ERK inhibitors reversed these effects. Moreover, we found that activation of PAR4 in ESCC cells significantly inhibited cell proliferation and induced apoptosis. These findings suggest that PAR4 plays a potential tumor suppressor role in ESCC cells and represents a potential therapeutic target of this disease.